Agathotanaididae (Crustacea: Tanaidacea) from the Angola Basin - Guerrero-Kommritz, Jürgen (Zootaxa, 2003)
The family Agathotanaididae Lang, 1971 has a worldwide distribution, with only three species known from the Angola Basin: Paranarthrura insignis Hansen, 1913, Paranarthrura intermedia Kudinova-Pasternak, 1982 and Paranarthura angolensis Guerrero-Kommritz, Schmidt & Brandt, 2002. Furthermore, three additional species are reported from the region: one each of Agathotanais, Metagathotanais and Paragathotanais. Agathotanaididae is represented by four of its five genera in this area.